Sustainable dairy production - Jong, Peter de , 1965- (Wiley-Blackwell, 2013)
"This book offers a comprehensive overview of the state of the art in sustainable dairy production, helping the industry to develop more sustainable dairy products, through new technologies, implementing life cycle analysis, and upgrading and optimization of their current production lines. It aims to stimulate process innovations, taking into account environmental, economic and public relations benefits for companies. Topics covered include: How to set up a sustainable production line How to quantify the carbon foot print of a dairy product by using life cycle analysis Current technologies to improve the carbon foot print What measures can be taken to reduce the global warming potential of the farm Reduction of water use in dairy production Marketing sustainable dairy products Bench marking of dairy products against other food products Potential future technological developments to improve the carbon foot print for the following decades "-- Provided by publisher